Trends in the consumption rates of benzodiazepines and benzodiazepine-related drugs in the health region of Lleida from 2002 to 2015 - Torres-Bondia, F.; de Batlle, J.; Galván, L.; Buti, M.; Barbé, F.; Piñol-Ripoll, G. (BMC public health, 2020)
Background The high prevalence and long-term use of benzodiazepines (BZDs) treatment are debated topics because of the risk they can cause to the patients. Despite the current information on the risk-benefit balance of these drugs, their consumption remains particularly high. We determined the trend in the consumption prevalence of benzodiazepines (BZDs) and drugs related to BZDs (Z-drugs) in the population of the Health Region of Lleida to explore patterns of use and the associated characteristics associated between 2002 and 2015. Methods An analysis of secular trends was carried out between 2002 and 2015; the databased included all individuals from the Health Region of Lleida, which had 358,157 inhabitants in 2015, that consumed BZDs. The consumption of BZDs was evaluated using prescription billing data from the Public Health System. All types of BZDs and BZD analogues that had been approved by the drug agency were included. Trends by age and sex were investigated. Results Over the whole study period, a total of 161,125 individuals accounted for 338,148 dispensations. Overall, 59% were women, and the mean age was 56 years. The dispensing prevalence of BZDs use in 2015 was 14.2% overall —18.8% in women and 9.6% in men—and was 36% in those over 65 years. According to the half-life of BZDs, the prevalence of short-intermediate BZD use, intermediate-long BZD use, and Z-drugs use was 9.7, 5.5 and 0.8%, respectively. The evolution of the annual prevalence of BZD dispensing showed a progressive decline, from 15.3% in 2002 to 14.2% in 2015, which was attributed to a decrease in the consumption of intermediate-long half-life BZDs (8.0% vs. 5.5%) and Z-drugs (1.4% vs. 0.8%). Conclusion The dispensing prevalence of BZDs and Z-drugs was high, although a small reduction was observed during this time period. The dispensing prevalence was especially high in the population over 65, despite the risk of cognitive decline and falls. Integral actions are required to lower the BZD prescription rate.